Bridging the Eemployment Gap of people with disabilities in Portugal through a training and skill development no-code platform: developing a no-code training and skill development platform - Selimagic, Edin (2023)
This thesis presents the Empower Ability project, a platform designed to enhance employment opportunities for individuals with disabilities in Portugal. Through in-depth research and collaboration with various stakeholders, the project identifies gaps in employment systems and develops a tailored solution. Utilizing agile and lean methodologies, Empower Ability employs a user-centric approach, ensuring fast development and responsiveness to stakeholder feedback. The project aims to bridge employment gaps for individuals with disabilities by providing essential training for inclusivity in the job market. The collaboration with partner organizations ensures the project's adaptability and potential for real-world impact, making it a practical solution for social change.